Cross-cultural insights on computational thinking in geometry: Indonesian and Japanese students’ perspectives - Prahmana, Rully Charitas Indra; Kusaka, Satoshi; Peni, Nur Robiah Nofikusumawati; Endo, Hiroyuki; Azhari, Ahmad; Tanikawa, Kanako (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Current research indicates the presence of highly skilled and motivated students with robust computational thinking backgrounds seeking opportunities to leverage their expertise in driving innovation and success in this era. These studies also reveal that students' computational thinking skills vary widely depending on educational resources, curriculum emphasis, and individual aptitude. Nonetheless, there is a growing recognition of the importance of fostering these skills, with efforts underway to integrate them more comprehensively into education systems worldwide, including in Indonesia and Japan, as representatives of developing and developed countries. Therefore, assessing the competency of computational thinking in these two countries would be intriguing. The descriptive qualitative research method was employed to delineate the computational thinking competencies of students in Indonesia and Japan. Student worksheets, specifically designed for this purpose, were utilized to gauge the development of these competencies during the learning process using the Scratch application. The results revealed that students employed various strategies in solving the given geometry problems. On the other hand, geometry is one of the mathematics topics that can identify students' computational thinking using this application. These findings were utilized to categorize students' computational thinking skills in the two countries and to identify potential obstacles students experienced in their efforts to enhance these skills. Nevertheless, these constraints offer significant insights into potential areas for future investigation and enhancement. Subsequent endeavors could prioritize conducting experiments by implementing specific learning approaches or methods that have demonstrated effectiveness in improving students' computational thinking skills. This study not only underscores the potential for expanding research on students' computational thinking skills but also provides an overview of the learning process, learning culture, and students' competence in solving geometry problems with tiered difficulty levels using their computational thinking skills.